Updated checklist of the amphibians from Loreto Department - Aguilar, César A. (2021)
This paper presents an updated list of the amphibians occurring in the department of Loreto, Peru, including information on conservation status, endemic species and areas with information gaps. Herpetological literature, databases and the collection of the Department of Herpetology of the Natural History Museum of the National University of San Marcos were used to update the species list. A total of 232 species were recorded, with anurans (toads and frogs) representing 96% of amphibians in Loreto. eighteen species are endemic to Loreto while the vast majority (208 species) have an altitudinal distribution below 500 m. Ten species are in threatened categories and four are near threatened according to international criteria; while four are considered as threatened and six as near threatened according the national list. Mayor information gaps are observed in areas near the borders with Brazil and Colombia.